Synthesis and crystal structure of 2-methoxy-4,6-bis(4-nitrophenoxy)-1,3,5-triazine - Yuanyuan, Huang; Fang, Bai; Guowei, Gao; Jian, Men (European Journal of Chemistry, 2012)
The novel compound, 2-methoxy-4,6-bis(4-nitrophenoxy)-1,3,5-triazine has been synthesized starting from 2,4,6-trichloro-1,3,5-triazine and characterized by 1H NMR, 13C NMR, IR, mass spectroscopy and elemental analysis. The single crystal of the title compound was obtained and subjected to X-ray diffraction analysis. The single crystal data illustrates that it belongs to the monoclinic system, space group C2/c with a = 13.818(3) Å, b = 7.8964(16) Å, c = 30.718(6) Å, β = 96.52(3) o, V = 3330.0(12) Å3, Z = 8, Dc = 1.537 g/cm3, C16H11N5O7, Mr = 385.30, µ (MoKα) = 0.124 mm−1, F(000) = 1584, the final R = 0.0489 and wR = 0.1821 for 2491 observed reflections with I>2σ(I).